2014
DOI: 10.1002/pamm.201410487
|View full text |Cite
|
Sign up to set email alerts
|

A one shot method for divertor target shape optimization

Abstract: Shape optimization methods, as commonly applied in aerodynamic design applications, have recently been adapted for use in nuclear fusion divertor target design. The resulting algorithms are very efficient compared to the standard use of numerical edge plasma simulations as analysis tools only. In this paper, we highlight some numerical aspects of the underlying algorithm, focusing on a correct, nine‐point discretization of the fluxes and the need for an adjoint pressure correction equation. (© 2014 Wiley‐VCH V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Given these promising results, further progress can now be made towards computationally affordable simulations of reactor‐relevant plasmas. Concerning numerics, the first step should be the introduction of a nine‐point stencil to accurately capture the isotropic‐neutral transport in non‐orthogonal grid geometries . Secondly, a grid extending up to the vessel wall is necessary to model the neutrals in realistic test cases.…”
Section: Discussion and Outlookmentioning
confidence: 99%
See 2 more Smart Citations
“…Given these promising results, further progress can now be made towards computationally affordable simulations of reactor‐relevant plasmas. Concerning numerics, the first step should be the introduction of a nine‐point stencil to accurately capture the isotropic‐neutral transport in non‐orthogonal grid geometries . Secondly, a grid extending up to the vessel wall is necessary to model the neutrals in realistic test cases.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…It should be noted that, in contrast to the plasma, neutrals are transported isotropically, therefore requiring a nine‐point stencil for their discretization . As this feature is currently absent in the SOLPS‐ITER code, we perform this benchmark on an orthogonal grid, using a so‐called slab case.…”
Section: Comparison To Eirene Kinetic Simulation Of Neutralsmentioning
confidence: 99%
See 1 more Smart Citation
“…For further details on deriving the exact adjoint state equations, the reader is referred to Ref. []. Finally, using the adjoint of the linearization with respect to the design variables ∂ ϕ c * ( ϕ , q ), it is found that the gradient can be expressed in the following way: trueJ^()ϕ=ϕscriptJ(),ϕq+ϕc*(),ϕqq*. …”
Section: Optimizationmentioning
confidence: 99%
“…Therefore, the inverse transformation G´1 2 will be used to transform fluxes over iso-x and iso-y lines back to fluxes in the pθ, rq coordinate system and discretize the equations there. The computational stencil is then extended to compute correction terms resulting from the nonalignment of the radial lines with the coordinate axis e r [32]. It is for this reason that the plasma edge equations in section 3.3 will be presented in the pθ, rq-coordinate system, with the metric coefficients h θ , h r , and the Jacobian ?…”
Section: A Coordinate Transformation For Anisotropic Plasma Edge Tranmentioning
confidence: 99%